1998
DOI: 10.1289/ehp.9810693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone and other pollutants on the pulmonary function of adult hikers.

Abstract: This study evaluated the acute effects of ambient ozone (O3), fine particulate matter (PM2.5), and strong aerosol acidity on the pulmonary function of exercising adults. During the summers of 1991 and 1992, volunteers (18-64 years of age) were solicited from hikers on Mt. Washington, New Hampshire. Volunteer nonsmokers with complete covariates (n = 530) had pulmonary function measured before and after their hikes. We calculated each hiker's posthike percentage change in forced expiratory volume in 1 sec (FEV1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(35 citation statements)
references
References 26 publications
(45 reference statements)
0
33
1
1
Order By: Relevance
“…Other factors may increase the susceptibility to the effects of O 3 , such as outdoor physical activity. For example, the study of Korrick et al mentioned above found that hiking was a modifier of the effect of O 3 on lung function 38. While the lack of activity pattern data in our study is a concern, we have no reason to believe this could upwardly bias our effect, and the likely direction of the bias is downward 50.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Other factors may increase the susceptibility to the effects of O 3 , such as outdoor physical activity. For example, the study of Korrick et al mentioned above found that hiking was a modifier of the effect of O 3 on lung function 38. While the lack of activity pattern data in our study is a concern, we have no reason to believe this could upwardly bias our effect, and the likely direction of the bias is downward 50.…”
Section: Discussionmentioning
confidence: 58%
“…A study evaluating the effects of ambient O 3 on 530 non-smoking hikers, aged 18–64, found significant associations between O 3 exposure and declines in FVC and FEV 1 38. When divided into four age categories, no difference in responsiveness to O 3 was found, suggesting that the associations found for the entire cohort are representative of the oldest age group (ages 48–64) for this sample population.…”
Section: Discussionmentioning
confidence: 76%
“…A higher effect of long-term air pollution exposure on physically active people could be linked to higher pulmonary ventilation and more outdoor exposure, with a consequent higher exposure load of polluted urban air. Other studies have reported exacerbation of asthma symptoms and decrease in lung function in athletes and hikers in response to elevated levels of air pollutants 31 32…”
Section: Discussionmentioning
confidence: 97%
“…Increased ambient levels of ozone and PM 2.5 have been associated with reduced lung function, [1][2][3][4][5][6][7] worsening asthma symptoms, [8][9][10][11] asthma-related emergency department visits, [12][13][14][15][16][17][18][19][20] and hospitalizations. [21][22][23][24][25] Little is known, however, about the association of ambient air pollutants with a very severe asthma episode requiring intensive care unit (ICU) admission.…”
mentioning
confidence: 99%